The importance of social support in times of COVID-19 and its protective factor for adolescents’ anxiety - Sæunn Ýr Óskarsdóttir 1993- (2023)
Adolescents’ daily life was greatly disturbed by social restriction in Iceland during COVID-19. They were prohibited from attending school in person or meeting friends and relatives. Studies have reported worse mental health in adolescents during COVID-19. It is essential, and the study’s aim to examine if perceived social support from parents or friends can act as a protective factor for adolescent anxiety. In this population-based study with a survey design, a sample was obtained from the LIFECOURSE study. The sample comprised 422 adolescents (57.5% girls) born in 2004 and resided in Iceland in 2017. The adolescents answered a survey about their well-being in COVID-19 between October 14, 2020, and April 16, 2021. A chi-square test was used to determine if parental or friend support could act as a protective factor for anxiety, and a t-test for the mean difference. Results indicate that parental support could act as a protective factor for anxiety, but only for girls. Girls were more anxious than boys and felt more friend support than boys. Friend support, however, did not affect adolescents’ anxiety. These results could be useful for parents and healthcare professionals to lessen the effects of anxiety for girls in times of crisis and in normal times. Keywords: Parental support, friend support, anxiety, gender, COVID-19. Líf íslenskra ungmenna varð fyrir verulegum áhrifum vegna félagslegra takmarkanna í COVID-19. Þeim var meinað að mæta í skólann í eigin persónu eða hitta vini og ættingja. Rannsóknir hafa greint frá versnun andlegra líðan ungmenna í COVID-19. Það er því nauðsynlegt, og markmið rannsóknarinnar að rannsaka hvort skynjaður félagslegur stuðningur frá foreldrum eða vinum geti verið verndandi þáttur gegn kvíða ungmenna. Í þessari þýðis rannsókn með spurningarsniði var fengið úrtak frá LIFECOURSE rannsókninni. Úrtakið samanstóð af 422 ungmennum (57,5% stúlkur) fædd 2004 sem voru með búsetu á Íslandi 2017. Ungmennin svöruðu spurningakönnun um vellíðan sína í COVID-19 sem fór fram 14. október 2020 ...